Self-Organisation Network (SON) Dengan Mekanisme Load Balancing - Ardian Ulvan; Melvi Ulvan; Robert Bestak (Jurnal Rekayasa Elektrika, 2018)
Load balancing is one of the mechanism used in the self-organization network (SON) to balance the traffic at the overloaded base station with the adjacent low-loaded base station. Load balancing is done by adjusting the handover parameters (metric) to obtain the optimal traffic balance. In this work, the adjusted parameters are the capacity of the cell. Cell capacity is strongly influenced by the bandwidth, modulation type, and the bit rate used by the user. The performance of load balancing was tested by a simulation and network test-bed measurement. The testing results on the Long-Term Evolution Advanced network showed the greater the bandwidth the greater the capacity of the cell. Moreover, the larger type of modulation, the cell capacity will also be greater. On the other hand, the greater bit rate used by the user, then the cell capacity will decrease. The calculation analysis of cell capacity is taken as the basic operation for load balancing procedure. A load balancing process algorithm is introduced to describe the mentioned procedure. The algorithm also considers the ping-pong effect that might occur due to the delay on the handover process.